Implementing of subject jigsaw learning model and its impact on students’ achievement in Embryology course - M. Haviz; L. Lufri (University of Muhammadiyah Malang, 2019)
Subject jigsaw has been identified as one of alternative model to teach difficult materials such as embryology. This study aimed to analyze the impact of the subject jigsaw model on students’ achievement. This quasi-experimental study employed post-test only control group design. As many as 84 students from the fifth semester in Biology Department of IAIN Batusangkar were involved as the sample. They were grouped in three classes which were taught using subject jigsaw model, jigsaw model, and conventional (control). The instruments were observation sheet and test. The cooperative skills and student learning outcome data were analyzed using ANOVA and least significance difference (LSD). The results showed that cooperative skills of students, at beginner, intermediate, and advanced levels, who learn with subject jigsaw are higher than those learning with successive Jigsaw of 3.10, 3.21, and 2.99. Furthermore, the students’ learning outcomes, who taught with subject jigsaw were significantly different from other treatments (F = 28.590; p-value < 0.05). Based on the LSD results showed that the students achievement on subject jigsaw model was better than the others. Thus, subject jigsaw model is recommended to implement in embryology course.